Electronic dynamics in low-dimensional materials - Deng, Tianqi (2016)
In this work, electronic dynamics in low-dimensional systems are studied. The main objective of this work is to understand the role of electronic structures along confined dimensions in low-dimensional materials. To achieve the goal, graphene saddle point excitons, σ band excitons in graphene multilayer structures, scaling law of many-body interactions in carbon nanotubes and graphene nanoribbons are studied as object systems. This research establishes an analytic model describing the role of electronic structures perpendicular to the quasi-2D material plane, and demonstrating the importance of this role. The finite thickness of electron wave function is found to be key factor in correctly determining the binding of excitons while the inter-layer coupling also plays significant role in layered structures. This quasi-2D nature also leads to a non-hydrogenic exciton spectrum which should be general for all quasi-2D materials. This work also correlates the geometry with scaling behavior of quasi-1D systems. It is demonstrated that the distinct power law behavior between ZCNTs and AGNRs should be attributed to the geometry difference. The results of this research imply that electronic structures along confined dimensions in low-dimensional materials are fundamental to their electronic dynamics including excitonic properties. The models established in this work are potentially applicable in general low-dimensional materials.